2023
DOI: 10.1021/acs.jchemed.2c00720
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Chemistry Students’ Perceived Abilities and Declarative Knowledge on Some Basic Aspects and Concepts of Spectroscopy

Olga A. Stambouli,
Sofia S. Pegka,
Ioannis P. Gerothanassis
et al.

Abstract: Spectroscopic methods of molecular structure identification and analysis constitute part of inorganic, organic, analytical, and physical chemistry in both undergraduate and postgraduate chemistry curricula. Despite the importance and complexity of the relevant concepts, it is only recently that studies on spectroscopy have started to appear in the education literature. These studies have focused on student interpretation of spectra. The purpose of this study was to deal with further fundamental issues underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…These findings suggest the need for more research A recent study investigated students' self-perceptions of their knowledge and declarative knowledge of basic concepts of UV, IR, NMR, and MS spectroscopic methods. 21 Stambouli and colleagues 21 suggested that students have several difficulties understanding the basic concepts of spectroscopy. 21 It was reported that students believed they understood mass spectrometry the least and understood IR spectroscopy the most.…”
Section: Students' Understanding Of Light and Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest the need for more research A recent study investigated students' self-perceptions of their knowledge and declarative knowledge of basic concepts of UV, IR, NMR, and MS spectroscopic methods. 21 Stambouli and colleagues 21 suggested that students have several difficulties understanding the basic concepts of spectroscopy. 21 It was reported that students believed they understood mass spectrometry the least and understood IR spectroscopy the most.…”
Section: Students' Understanding Of Light and Spectroscopymentioning
confidence: 99%
“…21 Stambouli and colleagues 21 suggested that students have several difficulties understanding the basic concepts of spectroscopy. 21 It was reported that students believed they understood mass spectrometry the least and understood IR spectroscopy the most. Despite believing they had an appreciable understanding of both IR and NMR, students demonstrated low declarative knowledge about these spectroscopies.…”
Section: Students' Understanding Of Light and Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation